Alternative Oxidase Capacity of Mitochondria in Microsporophylls May Function in Cycad Thermogenesis. Issue 2 (27th March 2019) - Ito-Inaba, Yasuko; Sato, Mayuko; Sato, Mitsuhiko P.; Kurayama, Yuya; Yamamoto, Haruna; Ohata, Mizuki; Ogura, Yoshitoshi; Hayashi, Tetsuya; Toyooka, Kiminori; Inaba, Takehito
Abstract : Enlarged mitochondria with increased rates of alternative respiration may account for the striking heat-producing ability of male cones in the gymnosperm Cycas revoluta. Abstract: Cone thermogenesis is a widespread phenomenon in cycads and may function to promote volatile emissions that affect pollinator behavior. Given their large population size and intense and durable heat-producing effects, cycads are important organisms for comprehensive studies of plant thermogenesis. However, knowledge of mitochondrial morphology and function in cone thermogenesis is limited. Therefore, we investigated these mitochondrial properties in the thermogenic cycad species Cycas revoluta . Male cones generated heat even in cool weather conditions. Female cones produced heat, but to a lesser extent than male cones. Ultrastructural analyses of the two major tissues of male cones, microsporophylls and microsporangia, revealed the existence of a population of mitochondria with a distinct morphology in the microsporophylls. In these cells, we observed large mitochondria (cross-sectional area of 2 μm 2 or more) with a uniform matrix density that occupied >10% of the total mitochondrial volume. Despite the size difference, many nonlarge mitochondria (cross-sectional area <2 μm 2 ) also exhibited a shape and a matrix density similar to those of large mitochondria. Alternative oxidase (AOX) capacity and expression levels in microsporophylls were much higher than those in microsporangia. The AOX genes expressed in male cones revealed two different AOX complementary DNA sequences: CrAOX1 and CrAOX2 . The expression level of CrAOX1 mRNA in the microsporophylls was 100 times greater than that of CrAOX2 mRNA. Collectively, these results suggest that distinctive mitochondrial morphology and CrAOX1-mediated respiration in microsporophylls might play a role in cycad cone thermogenesis.